2017
DOI: 10.1016/j.algal.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prediction of digestible protein content of marine microalgae (Nannochloropsis granulata) meals for Pacific white shrimp (Litopenaeus vannamei) and rainbow trout (Oncorhynchus mykiss)

Abstract: READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/eng/copyright Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Historically, in most aquaculture feeds, proteins and lipids are mainly supplemented with fish meal and fish oil. However, in recent years, due to the fall of fisheries, there is low availability, and as a result, its enormous demand has increased its costs (Castillo‐Lopez, Espinoza‐Villegas, & Viana, 2016; FAO, 2014; Tibbetts, Yasumaru, & Lemos, 2017). Therefore, in fish aquaculture especially when culturing different species, alternative ingredients of animal and vegetable origins are sought to replace with those obtained from fish meal and fish oil (Castillo‐Lopez et al, 2016; Desai et al., 2012; Tacon & Metian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, in most aquaculture feeds, proteins and lipids are mainly supplemented with fish meal and fish oil. However, in recent years, due to the fall of fisheries, there is low availability, and as a result, its enormous demand has increased its costs (Castillo‐Lopez, Espinoza‐Villegas, & Viana, 2016; FAO, 2014; Tibbetts, Yasumaru, & Lemos, 2017). Therefore, in fish aquaculture especially when culturing different species, alternative ingredients of animal and vegetable origins are sought to replace with those obtained from fish meal and fish oil (Castillo‐Lopez et al, 2016; Desai et al., 2012; Tacon & Metian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Table 5 a summary of the studies is presented where data on lipid and fatty acid digestibility have been reported. Among the literature, most assessments were of the diet digestibility, with only a few studies reporting the ingredient digestibility of any of the SCO resources [15,36,87,101,116]. Despite that, it is still possible to infer important aspects of the digestibility of the different SCOs from the diet digestibility data.…”
Section: Digestibilitymentioning
confidence: 99%
“…(Venkataraman & Becker 1985). Notwithstanding, very little information about the digestibility of macro-and microalgae protein for shrimp is available (Tibbetts et al 2017). In addition, their fatty acid profile and, especially the large amount of essential polyunsaturated fatty acids, such as EPA, ARA or DHA, also play a key role in the evaluation of their nutritional quality (Reitan et al 1997).…”
Section: Bioflocmentioning
confidence: 99%